Banking crisis management in the EU: An interim assessment - Jean Pisani-Ferry; André Sapir (Bruegel, 2009)
The European Union was institutionally ill-prepared to manage the 2007-2008 financial crisis, with an inadequate architecture for resolving problems within the European single financial market. Throughout the period 2007-2009 the situation in the EU has been characterised by a lingering lack of transparency, not only vis-à-vis market participants and the public, but also among policy-making institutions. Management of coordination has been ad hoc, but, remarkably, it has not been impeded by the divide between the euro area, and the main financial centre of London. Crisis management has mostly taken place according to the assignment of competences in the EU: the European Central Bank and national central banks have provided liquidity in their respective jurisdictions, national governments have stepped in to ensure financial stability, and the European Commission has enforced competition disciplines. So far, policy performance has been better than expected given the sub-optimal nature of EU financial institutional arrangements.
Keywords: 330; Bankenkrise; Finanzsystem; Marktintegration; Krisenmanagement; Bankenregulierung; EU-Staaten